Conrad and language - Baxter, Katherine Isobel 1976-; Hampson, Robert (Edinburgh University Press, 2016)
The essays in this collection examine Conrad's engagement with specific lexical sets and terminology – maritime language, the language of terror, and abstract language; issues of linguistic communication – speech, hearing, and writing; and his relationship to specific languages